Femtosecond Laser Fabricated Elastomeric Superhydrophobic Surface with Stretching-Enhanced Water Repellency - Huan Yang; Kaichen Xu; Changwen Xu; Dianyuan Fan; Yu Cao; Wei Xue; Jihong Pang (Nanoscale Research Letters, 2019)
Abstract Highly stretchable and robust superhydrophobic surfaces have attracted tremendous interest due to their broad application prospects. In this work, silicone elastomers were chosen to fabricate superhydrophobic surfaces with femtosecond laser texturing method, and high stretchability and tunable adhesion of the superhydrophobic surfaces were demonstrated successfully. To our best knowledge, it is the first time flexible superhydrophobic surfaces with a bearable strain up to 400% are fabricated by simple laser ablation. The test also shows that the strain brings no decline of water repellency but an enhancement to the superhydrophobic surfaces. In addition, a stretching-induced transition from “petal” state to “lotus” state of the laser-textured surface was also demonstrated by non-loss transportation of liquid droplets. Our results manifest that femtosecond laser ablating silicone elastomer could be a promising way for fabricating superhydrophobic surface with distinct merits of high stretchability, tunable adhesion, robustness, and non-fluorination, which is potentially useful for microfluidics, biomedicine, and liquid repellent skin.